2007
DOI: 10.1042/bj20070543
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated association of plastid division protein FtsZ1 with thylakoid membranes in Arabidopsis thaliana

Abstract: FtsZ is a key protein involved in bacterial and organellar division. Bacteria have only one ftsZ gene, while chlorophytes (higher plants and green alga) have two distinct FtsZ gene families, named FtsZ1 and FtsZ2. This raises the question of why chloroplasts in these organisms need distinct FtsZ proteins to divide. In order to unravel new functions associated with FtsZ proteins, we have identified and characterized an Arabidopsis thaliana FtsZ1 loss-of-function mutant. ftsZ1-knockout mutants are impeded in chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
(59 reference statements)
3
26
1
Order By: Relevance
“…Interestingly, the apparent plasticity of FtsZ coassembly in vitro is consistent with genetic studies showing that chloroplast FtsZ filaments assemble under a wide range of in vivo stoichiometries, although significant deviations from the wild type stoichiometry alters FtsZ filament morphology and perturbs plastid division (17,19,20,24,61). Nevertheless, the ability of FtsZ1 and FtsZ2 to coassemble at different stoichiometries raises the intriguing possibility that the degree of heteropolymerization and/or bundling may be regulated in vivo as a means of regulating FtsZ filament morphology and hence Z ring constriction and dynamics.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, the apparent plasticity of FtsZ coassembly in vitro is consistent with genetic studies showing that chloroplast FtsZ filaments assemble under a wide range of in vivo stoichiometries, although significant deviations from the wild type stoichiometry alters FtsZ filament morphology and perturbs plastid division (17,19,20,24,61). Nevertheless, the ability of FtsZ1 and FtsZ2 to coassemble at different stoichiometries raises the intriguing possibility that the degree of heteropolymerization and/or bundling may be regulated in vivo as a means of regulating FtsZ filament morphology and hence Z ring constriction and dynamics.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, the ability of FtsZ1 and FtsZ2 to coassemble at different stoichiometries raises the intriguing possibility that the degree of heteropolymerization and/or bundling may be regulated in vivo as a means of regulating FtsZ filament morphology and hence Z ring constriction and dynamics. Such regulation may be necessary because plants have multiple plastid types that vary greatly in size and division activity; perhaps the relative levels of FtsZ1 and FtsZ2 vary in different plastid types or at different stages of development (61). In this context, it is interesting to note that complete FtsZ2 rings are occasionally observed in small plastids of ftsZ1 null mutants (25), but the converse is not true (19).…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that a cytoskeleton-like FtsZ network in chloroplasts aids in maintaining the chloroplast structure. Overexpression of FtsZ has been demonstrated to lead to alterations of the chloroplasts in Arabidopsis (Arabidopsis thaliana) leaves (El-Kafafi et al, 2008) that are similar to those observed here for desiccated P. patens gametophores.…”
Section: Alterations In Cellular Structure Help To Limit Desiccation supporting
confidence: 61%
“…We could not confirm earlier reports of altered starch accumulation and granule number in arc3, arc5, arc6, and arc10 mutants (Austin and Webber, 2005;El-Kafafi et al, 2008); thus, there is at present no good evidence that components of the chloroplast division apparatus act as primers for granule initiation. Our observations do not allow us to distinguish between other possible priming mechanisms.…”
Section: Granule Initiation Is Infrequent In Mature Leavescontrasting
confidence: 55%
“…However, there are indications that some of the ARC proteins may influence starch accumulation. Arabidopsis arc3, arc5, arc6, and arc10 mutants were reported to have increased starch accumulation, whereas plants overexpressing FtsZ1 (ARC10) have no starch granules (Austin and Webber, 2005;El-Kafafi et al, 2008). Overexpression of FtsZ in potato (Solanum tuberosum) tubers resulted in smaller plastids apparently containing fewer, larger starch granules (de Pater et al, 2006) and rice (Oryza sativa) endosperm misexpressing FtsZ proteins contains granules of abnormal sizes and shapes (Yun and Kawagoe, 2010).…”
Section: Relationship Between Starch Granule Number and Chloroplast Vmentioning
confidence: 99%